Is bone marrow biopsy and aspiration still mandatory when 18F-FDG PET/CT is available for the initial assessment of bone marrow metastasis in pediatric Ewing sarcoma? - Du, Yifei; Zhao, Zhenzhen; Yang, Chao (Frontiers in Oncology, 2024)
Purpose To compare the diagnostic value of 18F-fluorodeoxyglucose-positron emission tomography/computed tomography (18F-FDG PET/CT) and bone marrow biopsy and aspiration (BMBA) for evaluating bone marrow metastases (BMM) in newly diagnosed pediatric Ewing sarcoma (ES). Material and methods To assess the diagnostic accuracy of 18F-FDG PET/CT against BMBA for marrow infiltration in ES patients, a retrospective analysis encompassed 103 ES patients from the Children’s Hospital of Chongqing Medical University, spanning nine years, who underwent both 18F-FDG PET/CT and BMBA at the point of diagnosis. Results The median age of this study was 9.3(15 days to 17.1 years), 52(50.5%) patients were male. Among the cohort, 8 subjects received a BMM diagnosis via marrow cytology or histopathology, concomitant with positive 18F-FDG PET/CT findings. An additional 4 patients were identified with BMM solely through 18F-FDG PET/CT. No cytologically or histologically positive BMM were found in PET/CT-negative patients. Therefore, within this selected sample group, the 18F-FDG PET/CT imaging technique exhibited sensitivity of 100% and specificity of 95.8%. The five-year overall survival rate decreased from 57.5% among the entire cohort of patients to a mere 30% for individuals suffering from BMM. Conclusion Given these findings, the prevailing reliance on BMBA warrants reevaluation when 18F-FDG PET/CT is available, potentially heralding a shift towards less invasive diagnostic modalities in the management of ES.